PENERAPAN SISTEM ZONASI DALAM PENERIMAANCALON PESERTA DIDIK BARU DI BALI - I Nyoman Suandika (Universitas Mahendradatta, 2022)
Education is one of the problems that is often the center of attention in Indonesia because education is very important in improving the intelligence of the nation's life in Indonesia. Basically, according to the Constitution of the Unitary State of the Republic of Indonesia in Article 1 paragraph (3) it is stated that the Indonesian state is a legal state which means that every act of the state and citizens must be based on and based on law. In the Preamble to the 1945 Constitution of the Republic of Indonesia, it is emphasized that the state has an obligation to educate the life of the Indonesian people. One of the efforts to improve and equalize the quality of education in Indonesia is to implement a zoning system in the process of admitting new students. The provisions for the zoning system are contained in the Regulation of the Minister of Education and Culture Number 14 of 2018. With the enactment of this regulation in Indonesia, it seems that not 100 percent of parents or guardians of students have accepted the regulation. So that it reaped controversy, including the Province of Bali as one of the provinces in the Unitary State of the Republic of Indonesia. The problem is what are the factors that influence the controversy over public attitudes with the application of zoning in new student admissions with the issuance of the Minister of Education and Culture Regulation Number 14 Year 218 of the Province of Bali and how the government has made efforts to overcome the zoning problem in the Province of Bali. This type of research uses empirical legal research methods using primary data and secondary data and tertiary data. The main factor causing the controversy is the high difference between favorite and nonfavorite schools in the province of Bali so far so that the implementation of the zoning policy is rejected by some people. For this reason, the efforts made by the government are to carry out intensive socialization related to the application of zoning that can reach all lines and layers of society which aims to increase public awareness to participate in supporting zoning policies in the process of new student admissions.